A Narrative Review of Early Oral Stepdown Therapy for the Treatment of Uncomplicated Staphylococcus aureus Bacteremia: Yay or Nay?. (5th May 2020) - Dagher, Michael; Fowler, Vance G; Wright, Patty W; Staub, Milner B
Abstract: Historically, intravenous (IV) antibiotics have been the cornerstone of treatment for uncomplicated Staphylococcus aureus bacteremia (SAB). However, IV antibiotics are expensive, increase the rates of hospital readmission, and can be associated with catheter-related complications. As a result, the potential role of oral antibiotics in the treatment of uncomplicated SAB has become a subject of interest. This narrative review article aims to summarize key arguments for and against the use of oral antibiotics to complete treatment of uncomplicated SAB and evaluates the available evidence for specific oral regimens. We conclude that evidence suggests that oral step-down therapy can be an alternative for select patients who meet the criteria for uncomplicated SAB and will comply with medical treatment and outpatient follow-up. Of the currently studied regimens discussed in this article, linezolid has the most support, followed by fluoroquinolone plus rifampin. Abstract : The role of oral antibiotics in the treatment of uncomplicated Staphylococcus aureus bacteremia is a subject of debate. We summarize key arguments both for and against their use and evaluate available evidence for the efficacy of specific oral antibiotic regimens.